The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1403637
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a full-time falling monitor for the elderly

Abstract: The article presents the early outcomes of the evaluation of an intelligent accelerometer unit (IAU) utilized for detecting the falling events of elderly people . The overall design of the monitor where the IAU is integrated is briefly exposed. The outcomes of a laboratory study carried out over 8 volunteers show that the device is able to distinguish true falling events from normal activities like fast walking or going up/downstairs. The influences of the subject and the environment have been taken into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 11 publications
1
25
0
1
Order By: Relevance
“…6 shows the acceleration and rotational rate of the trunk and thigh for sitting fast. Both a Amax and a Bmax are larger than thresholds used in [13], [5], [9], [7], and [3]. Therefore, sitting down fast is not distinguishable from a typical fall.…”
Section: Sit Down Fastmentioning
confidence: 93%
“…6 shows the acceleration and rotational rate of the trunk and thigh for sitting fast. Both a Amax and a Bmax are larger than thresholds used in [13], [5], [9], [7], and [3]. Therefore, sitting down fast is not distinguishable from a typical fall.…”
Section: Sit Down Fastmentioning
confidence: 93%
“…• The efficacy of the algorithm that is implemented by the control circuit to detect automatically the time of descent using some sensors (e.g., accelerometers (18)(19)(20)(21)(22)(23) , gyroscope (21,(24)(25) , load (26) ) (18,20,24,(27)(28)(29) . Here, the term "time of descent" is defined as the moment when the amputees cease to have control over their movements leading their body to hit the ground.…”
Section: 2mentioning
confidence: 99%
“…Prado [19] developed an intelligent 4 axis accelerometer unit (IAU) worn like a patch, fixed to the back at the height of the sacrum. The IAU was evaluated by Diaz [20] in a laboratory study carried out over 8 volunteers, it showed that the device was able to distinguish true falling events from normal activities like fast walking or going up/downstairs. Recently, Bourke proposed fall algorithms separately based on thresholds on both signals from a tri-axial accelerometer [21] and a biaxial gyroscope [22] and reached a performance of 100%.…”
Section: State Of the Artmentioning
confidence: 99%